Modification of smoothing in 4253H[T] - Khairol Azmi, Nurul Nisa'; Adam, Mohd Bakri; Shitan, Mahendran; Mohd Ali, Norhaslinda (AIP Publishing, 2016)
Some modified non-linear smoothers particularly 4253H[T] are explained in this paper. The modifications are focused on estimating the middle point of running median for even span by applying the following types of means; geometric, harmonic, quadratic and contraharmonic. The performance of the techniques is assessed by applying it to daily price index of a bank in Malaysia that issues sukuk for funding in Islamic banking and financial business. The results show that 4253H[T] with geometric mean modification is better than others in preserving variation and curve fitting.